Reducing CO2 footprint through synergies in carbon free energy vectors and low carbon fuels. (1st October 2016) - Wang, W.; Herreros, J.M.; Tsolakis, A.; York, A.P.E.
Abstract: Carbon-footprint from transport and power generation can significantly be improved when carbon free or reduced carbon energy carries are utilised that are compatible with the current technology of the internal combustion (IC) engines. The current study focuses on the reduction of diesel engine CO2 emissions by improving ammonia and hydrogen combustion through the incorporation of alternative fuel, diethyl glycol diethyl ether (DGE) as an oxygenated fuel blend and combustion enhancer. The aim of the work is to study the potential synergies between DGE and two carbon free energy vectors H2 and NH3 in reducing the environmental effects and contribute in decarbonising internal combustion engines. DGE's ignition properties (i.e. high cetane number) improved the H2 and NH3 combustion efficiencies via counteracting their high auto-ignition resistances, and also contributing in lowering the unburnt H2 and NH3 emissions to the atmosphere. This led in the reduction of CO2 by up 50% when 60–70% of diesel fuel is replaced with DGE, H2 and NH3 . Synergetic effects were also found between DGE and the gaseous fuels (i.e. hydrogen and ammonia) simultaneously decreasing the levels of PM, NOx, HC and CO emitted to the atmosphere; thus mitigating the health and environmental hazards associated to diesel engines. Graphical abstract: Highlights: DGE improved the ignition and combustion of H2 and NH3 for better HC fuel substitution. DGE's low temperature combustion suppressed the NOx emissions from improved H2 and NH3 combustion. Large carbonaceous reductions were achieved by applying the DGE assisted H2 and NH3 combustions. DGE's high oxygenation counteracted the oxygen dilution from gaseous fuelling at the air intake.